Judicial divergence in enforcing annulled arbitral awards under the New York Convention 1958 - Iyllyana Che Rosli; Tengku Chik Abu Bakar Tengku Ibrahim; Norhasliza Ghapa; Murshamshul Kamariah Musa; Asril Amirul Zakariah (Jurnal Hukum Novelty, 2026)
Introduction to the Problem: The enforcement of annulled foreign arbitral awards under the New York Convention 1958 (NYC 1958) presents a complex legal challenge due to the Convention's Contracting States’ divergence approach on its interpretation. Purpose/Study Objectives: The paper attempts to assess the extent of enforcement of awards vacated by its supervisory seat and to propose a harmonised interpretive method that is align with the goal or NYC 1958 while maintaining the diversity of national laws on the enforcement of annulled foreign awards. Design/Methodology/Approach: This paper adopts a doctrinal and comparative legal methodology. The doctrinal analysis analyses statutory frameworks and judicial reasoning underlying the territorialist, delocalised, and assessment approaches, while the comparative method examines how these models are applied across different jurisdictions. Findings: The territorialist approach, adopted by German courts, refuses to enforce awards vacated by its supervisory seat. The delocalised approach, adopted by French courts, supports enforcement by invoking Article VII and applying domestic law. The assessment approach, seen in Dutch, US, and English courts, involves evaluating annulment reasons on a case-by-case basis. This paper argues that the lack of harmonisation in the application of Article V (1) (e) results in divergent judicial practices. The Maximov’s case illustrates this divergence: French courts enforced the award, Dutch courts upheld enforcement after assessment, and the London High Court dismissed enforcement, requiring substantial proof of bias in annulment. The findings reveal inconsistencies in how Article V (1) (e) is applied, emphasising the need for clearer international guidelines to promote uniformity and predictability in the enforcement of annulled arbitral awards. This paper contributes to the existing literature by proposing an assessment-based framework, supported by clearer and more transparent criteria, to guide courts in evaluating annulments on their merits while preserving respect for the seat court’s decisions, when deciding on the enforcement of annulled awards. Paper Type: Research Article